2008
DOI: 10.1515/jpem.2008.21.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood Thyroxine and Thyroid Stimulating Hormone Screening for Congenital Hypothyroidism: How Useful Are They?

Abstract: Cord FT4 identifies only infants with severe CH. Cord TSH is more sensitive than cord FT4 screening. Capillary TSH dried blood spot testing on the 3rd-5th day is the most sensitive method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
(15 reference statements)
2
14
0
Order By: Relevance
“…[111213] Currently in some countries it has been chosen for the methods of choice in the screening program. [14]…”
Section: Introductionmentioning
confidence: 99%
“…[111213] Currently in some countries it has been chosen for the methods of choice in the screening program. [14]…”
Section: Introductionmentioning
confidence: 99%
“…Currently used for primary CHT screening in Singapore. More recent study from Abu Dhabi with DELFIA reagents showed cord fT4 to be insensitive, cord TSH to be more sensitive but specificity poorer than DBS [11].…”
Section: Cord Blood Dbs Collected At a Few Days Of Agementioning
confidence: 98%
“…In some countries, such as Finland and Malta, cord blood sampling is used for newborn screening testing according to early maternal and newborn discharge [12,13], but it has been evaluated that better results are obtained from samples collected by heel/hand prick at a later stage [14,15].…”
Section: Sample Collectionmentioning
confidence: 99%